2009
DOI: 10.1086/595834
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immune Response to Hantaan Virus Nucleocapsid Protein in the Acute Phase of Hemorrhagic Fever with Renal Syndrome: Correlation with Disease Severity

Abstract: Taken together with published data on the similar associations with neutralizing antibody, these data suggest that IFN-gamma-producing T cells may help reduce the risk of progression to acute renal failure caused by HTNV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 33 publications
1
48
2
Order By: Relevance
“…The CTL response in the two donors was directed to different epitopes on the HTNV nucleocapsid protein, and was restricted by a variety of HLA alleles, thus demonstrating a diverse HTNVspecific T-cell repertoire. T cell epitopes identified in our study were different from those identified in previous publications (8,20,23,24), possibly due to the mixed HLA backgrounds in each of the small cohorts. Another probable explanation is that the antiviral T-cell response is a dynamic process, with low or absent ELISPOT responses at hospital admission, reaching their peaks during a follow-up period of several weeks, that then wane over time (11,19).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The CTL response in the two donors was directed to different epitopes on the HTNV nucleocapsid protein, and was restricted by a variety of HLA alleles, thus demonstrating a diverse HTNVspecific T-cell repertoire. T cell epitopes identified in our study were different from those identified in previous publications (8,20,23,24), possibly due to the mixed HLA backgrounds in each of the small cohorts. Another probable explanation is that the antiviral T-cell response is a dynamic process, with low or absent ELISPOT responses at hospital admission, reaching their peaks during a follow-up period of several weeks, that then wane over time (11,19).…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we focused our investigations on the HTNV nucleocapsid protein, which has been shown to induce efficient protection against virus challenge in animal models (1,2,9), and stronger IFN-c-producing T-cell responses in patients with milder HFRS than in those with severe disease (22), because we were unable to collect enough blood samples from patients to study the T-cell responses to peptide antigens spanning the entire genome. We have analyzed the nucleocapsid-specific T-cell response in two HTNV-infected donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 In stark contrast, higher frequencies of IFNγ producing antiviral T cells during acute HTNV infection are linked to mild or moderate HFRS emphasizing the protective role of T cells. 69 The discrepancy between these results may be explained by the different methods used to visualize T cells. In general, tetramer staining reveals much higher virus-specific T cell frequencies than IFNγ ELISPOT and identifies virus-specific T cells irrespective of their function.…”
Section: Role Of Antiviral Immune Responses In Hantavirus-induced Patmentioning
confidence: 99%
“…Corticosteroids have been used to treat severe complications of hantavirus infection. 17 In view of the crucial role of T cells secreting IFN-␥ in the resolution of the disease, 18 amore targeted approachagainst TNF-␣ might be an option for severe hemorragic fever with renal syndrome.…”
Section: Discussionmentioning
confidence: 99%